2017 International Conference on Rehabilitation Robotics (ICORR) 2017
DOI: 10.1109/icorr.2017.8009215
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of muscle synergy structure during standing-up motion of healthy young, elderly and post-stroke patients

Abstract: Standing-up motion is an important daily activity. It has been known that elderly and post-stroke patients have difficulty in performing standing-up motion. The standing-up motion is retrained by therapists to maximize independence of the elderly and post-stroke patients, but it is not clear how the elderly and post-stroke patients control their redundant muscles to achieve standing-up motion. This study employed the concept of muscle synergy to analyze how healthy young adults, healthy elderly people and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 11 publications
4
18
0
Order By: Relevance
“…Eriksrud et al found that knee extension is a strong predictor of independence during STS transfer [37], and Lomaglio et al also showed that both knee extension and ankle dorsiflexion are related to STS performance [38]. In our previous study, it was found that poststroke patients delayed the peak time of synergy 2 and required larger hip and lumbar flexion to move forward compared with healthy controls [39].…”
Section: B Temporal Features Of Muscle Synergymentioning
confidence: 66%
“…Eriksrud et al found that knee extension is a strong predictor of independence during STS transfer [37], and Lomaglio et al also showed that both knee extension and ankle dorsiflexion are related to STS performance [38]. In our previous study, it was found that poststroke patients delayed the peak time of synergy 2 and required larger hip and lumbar flexion to move forward compared with healthy controls [39].…”
Section: B Temporal Features Of Muscle Synergymentioning
confidence: 66%
“…Similarly, the peak time also seemed to advance toward an earlier time in the motion progress. This reduced lag in peak times, together with the increased peak amplitude in normalized Synergy 2 (for hip raise), may explain the patient's motor recovery since former studies have found that the peak time of Synergy 2 delayed significantly after stroke onset when compared to that of healthy controls (Yang et al, 2017(Yang et al, , 2019. These former studies thereby insisted on teaching the patients the right time to raise their hips.…”
Section: Rehabilitation Of Muscle Synergymentioning
confidence: 95%
“…A minimum of six-week repetitive training can induce changes in the white matter to build new or augment existing synergies [ 53 , 106 , 121 ]. In the lower limb, while standing, stroke-affected patients and healthy individuals exhibited common synergies, since the stroke patients shifted the center of mass to maintain balance and their MS were similar to those of a healthy person [ 48 , 122 , 123 ]. In most studies, NNMF (multiplicative method) is used to study the synergies among stroke patients [ 51 , 52 , 107 , 109 ].…”
Section: Ms As a Physiological Marker For Neurorehabilitationmentioning
confidence: 99%